EXPLORING SPEAKING LEARNING STRATEGIES USED BY PROFICIENT STUDENTS OF TWELVE CLASS AT A STATE SENIOR HIGH SCHOOL IN JAKARTA - Muhammad Rifki; Yousef Bani Ahmad; Hilmansyah Saefullah (PROJECT (Professional Journal of English Education), 2023)
The aims of this research was to explore speaking learning strategies used by proficient students of twelve class at a state senior high school in Jakarta in 2022/2023 academic year. This research provide one research question: what is speaking learning strategies used by proficient students of twelve class at a state senior high school in Jakarta? The study was conducted by using quantitative research as the research design. The participants of this study were 72 top grade students of science and social class of a state senior high school in Jakarta. The instruments used in this study were speaking learning strategy questionaire that indicate speaking learning strategies proposed by Oxford (1990). The findings of this study found that proficient students of twelve class at a state senior high school used speaking learning strategies had 2,8 medium usage level of speaking learning strategies with the frequent speking learning strategies was metacognitive strategies in 3,2 medium usage level, second was affective strategies in 3,1 medium usage level, and the third was compensation strategis which had 2,9 medium usage level. So it could be conclude that metacognitive strategies was the dominant speaking learning stategies used by top grade of twelve class at a state senior high school. Keywords:  Proficients Students of Twelve Class; Speaking; Speaking Learning Strategies